Proyecto de factibilidad para la creación de una agencia de viajes y de turismo de aventura en la provincia de Imbabura con sede en la ciudad de Otavalo. - Salas López, Sonia Margarita (2013)
This project arises from the need to offer a new alternative tourists sightseeing in the city of Otavalo, due to the high number of tourists it receives annually, it is very important to identify your: needs, tastes and preferences to satisfy such to become constant visitors. Tourism in Ecuador has increased by 15% despite the crisis affecting the world, noting that becomes lucrative and with great potential to be exploited in most parts of the country. The market study offers an overview of the characteristics of current and potential visitors, generating data that allow us to probable investments